2006
DOI: 10.1590/s0085-56262006000300008
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism, inter-population and inter-specific variation in Nyssomyia intermedia (Lutz & Neiva) and Nyssomyia neivai (Pinto) (Diptera, Psychodidae, Phlebotominae)

Abstract: ABSTRACT. Polymorphism, inter-population and inter-specific variation in Nyssomyia intermedia (Lutz & Neiva) and Nyssomyia neivai (Pinto) (Diptera, Psychodidae, Phlebotominae). Nyssomyia intermedia (Lutz & Neiva) and Nyssomyia neivai (Pinto) are morphologically very close and both present great variation in some structures. The objective of this study is a description of the variation among the females of these species in populations from the States of Minas Gerais and São Paulo. The morphological structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(22 reference statements)
2
4
0
1
Order By: Relevance
“…neivai was similar while the number of rings in most of the specimens of the first species was higher compared to the second group. The findings in our study are in agreement with those of Marcondes (1996) and Andrade Filho et al (2006), who demonstrated that the number of spermathecae rings is higher in Ny. intermedia than in Ny.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…neivai was similar while the number of rings in most of the specimens of the first species was higher compared to the second group. The findings in our study are in agreement with those of Marcondes (1996) and Andrade Filho et al (2006), who demonstrated that the number of spermathecae rings is higher in Ny. intermedia than in Ny.…”
Section: Discussionsupporting
confidence: 93%
“…neivai and Ny. intermedia populations conducted by Andrade Filho et al (2006) showed, in corroboration with our findings, that the number of teeth in the cibarium varies among different populations so that it cannot be considered an appropriate feature in determining species discrimination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…neivai (Pinto, 1926) are morphologically very similar (Andrade-Filho et al 2006), so much so that Ny. neivai has been proposed as a junior synonym of Ny.…”
Section: Resumo Nyssomyia Intermediamentioning
confidence: 99%
“…Por essa razão, não raro, uma determinada espécie, após estudos mais detalhados, distingue-se em mais de um táxon (Marcondes 1998). Exemplos dessa natureza são os complexos identifi cados de Lutzomyia longipalpis (Lutz & Neiva) (Lanzaro et al 1993), Nyssomyia whitmani (Antunes & Coutinho) (Ready et al 1997) e Nyssomyia intermedia (Lutz & Neiva) (Marcondes 1996, 1997, Andrade-Filho et al 2006. Marcondes (1996Marcondes ( , 1997 As coletas de fl ebotomíneos foram realizadas em todas as localidades com armadilhas elétricas luminosas do tipo Falcão (modifi cada), entre as 18:00h e 6:00h, distribuídas em varanda de residência, galinheiro, chiqueiro, bananal, mata, túnel, toca de tatu, gruta e fendas de rocha, e apenas em Morretes, Guaraqueçaba, Paranaguá e Matinhos, com armadilha de Shannon, também com atrativo luminoso, instalada em mata das18:00h às 21:00h.…”
unclassified